Exercise and exercise training‐induced increase in autophagy markers in human skeletal muscle - Brandt, Nina (Physiol Rep, 2018)
Moderately trained male subjects (mean age 25 years; range 19–33 years) completed an 8‐week exercise training intervention consisting of continuous moderate cycling at 157 ± 20 W for 60 min (MOD; n = 6) or continuous moderate cycling (157 ± 20 W) interspersed by 30‐sec sprints (473 ± 79 W) every 10 min (SPRINT; n = 6) 3 days per week. Sprints were followed by 3:24 min at 102 ± 17 W to match the total work between protocols. A muscle biopsy was obtained before, immediately and 2 h after the first training session as well as at rest after the training session. In both MOD and SPRINT, skeletal muscle AMPK(T) (hr172) and ULK(S) (er317) phosphorylation was elevated immediately after exercise, whereas mTOR(S) (er2448) and ULK(S) (er757) phosphorylation was unchanged. Two hours after exercise LC3I, LC3II and BNIP3 protein content was overall higher than before exercise with no change in p62 protein. In MOD, Beclin1 protein content was higher immediately and 2 h after exercise than before exercise, while there were no differences within SPRINT. Oxphos complex I, LC3I, BNIP3 and Parkin protein content was higher after the training intervention than before in both groups, while there was no difference in LC3II and p62 protein. Beclin1 protein content was higher after the exercise training intervention only in MOD. Together this suggests that exercise increases markers of autophagy in human skeletal muscle within the first 2 h of recovery and 8 weeks of exercise training increases the capacity for autophagy and mitophagy regulation. Hence, the present findings provide evidence that exercise and exercise training regulate autophagy in human skeletal muscle and that this in general was unaffected by interspersed sprint bouts.